'It's A Social Thing, Not a Nature Thing': Popular Music Practices in Reykjavík, Iceland. (March 2015) - Prior, Nick
Over the last three decades, Iceland's reputation has been increasingly tied to the prominence of its popular music. Associated with an effervescent independent scene and the global successes of the band Sigur Rós and the singer Björk, the country has been positioned as one of the world's most vibrant cultural hotspots. With particular reference to Reykjavík, the paper aims to show how the city's spatial configuration favours the development of dense creative networks and attendant forms of knowledge, conflict, diversity and collaboration. It assesses the integrative nature of music education on the island, the formation of a small but influential punk scene and the global marketing of the country's music through an agile cluster of cultural agencies and intermediaries. Getting a sense of the city's routine musical practices, it will be argued, opens an aperture on the location of place-based musics within prevailing social and economic conditions.